Examining the Marketing Strategy of Celebrity-Founded Brands: A Case Study of Skims by Kim Kardashian - Li, Jiani (Transactions on Social Science, Education and Humanities Research, 2024)
As the trend of celebrity-founded brands rises, several celebrities attempt to create their own brand with the assistance of professionals, or to take on roles as creative directors of an existing brand. However, one may wonder why some of these brands achieve greater success than others, especially when the celebrities involved are equally well-kown. Through documentary research methods, this study reveals that there is a strong correlation between brand successfulness and the brand's marketing strategy. The conclusion is drawn from using the fashion brand Skims as an example of a typical celebrity-founded brand that employs effective offline and online marketing techniques. Skims has successfully established itself as a unique and welcoming fashion brand that is popular worldwide, emphasizing diversity and the ability to produce products in a wide range of body types and skin tones by developing successful brand positioning and segmentation. Nevertheless, all the above could still be improved through strategic positioning, relying less on celebrity presence, and using more creative marketing strategies, which shall be further discussed in this paper.